2014
DOI: 10.1039/c4cc04794j
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional optical waveguiding and luminescence vapochromic properties of 8-hydroxyquinoline zinc (Znq2) hexagonal microsheets

Abstract: Two-dimensional (2D) hexagonal microsheets of 8-hydroxyquinoline zinc (Znq2) were synthesized readily via a mixed solvent induced self-assembly method. The 2D optical waveguiding properties of the microsheets have been clearly revealed by both fluorescence microscopy and confocal microscopy. In addition, the reversible vapochromic properties of the microsheets have also been demonstrated when the Znq2 is exposed to HCl and NH3 vapors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The inset of the selected‐area diffraction (SAED) pattern in Figure 1d shows that the obtained Znq 2 flake possesses a high crystalline quality. To check the crystal structure of Znq 2 , X‐ray diffraction (XRD) measurement was carried out, as shown in Figure S3a, Supporting Information, and the results implied that the 2D nanosheets have single‐crystal structures, and the preferred growth direction of the nanosheets perpendicular to the substrate is [100], which is in agreement with the results reported by Sun et al [ 17 ] The PL spectra in Figure S3b, Supporting Information, revealed the feature emission peak of Znq 2 nanosheets located at 508 nm (excited by a laser source with a wavelength of 355 nm), and their corresponding UV–vis–IR absorption exhibited its high absorption efficiency within 200–250 nm but rapidly descended at the range of 250–800 nm, revealing its low absorption ability from violet to visible region. Namely, optical loss in the visible region is relatively low, revealing its good potential application for effective optical waveguides.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The inset of the selected‐area diffraction (SAED) pattern in Figure 1d shows that the obtained Znq 2 flake possesses a high crystalline quality. To check the crystal structure of Znq 2 , X‐ray diffraction (XRD) measurement was carried out, as shown in Figure S3a, Supporting Information, and the results implied that the 2D nanosheets have single‐crystal structures, and the preferred growth direction of the nanosheets perpendicular to the substrate is [100], which is in agreement with the results reported by Sun et al [ 17 ] The PL spectra in Figure S3b, Supporting Information, revealed the feature emission peak of Znq 2 nanosheets located at 508 nm (excited by a laser source with a wavelength of 355 nm), and their corresponding UV–vis–IR absorption exhibited its high absorption efficiency within 200–250 nm but rapidly descended at the range of 250–800 nm, revealing its low absorption ability from violet to visible region. Namely, optical loss in the visible region is relatively low, revealing its good potential application for effective optical waveguides.…”
Section: Resultssupporting
confidence: 85%
“…It has been suggested that the lasing modes in the hexagonal‐shaped Znq 2 nanosheets correspond to the quasi‐WGM modes, [ 17,21 ] where strong light confinement exists along the edges of the nanosheets and peak spacing is around 4 nm as in the measured lasing spectrum. [ 21 ] According to the theory of WGM, [ 22,23 ] the resonance wavelength for the N th mode in the hexagonal cavity can be calculated asλWGM=3ndN+6πθwhere d is facet separation, n is the refractive index, and tanθ=β3n24.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 For instance, some coordination and organometallic complexes restore their original colour and emission spectra in the presence of air or vacuum due to the evaporation of the VOCs to which they have been exposed. [6][7][8] Therefore, the development of vapochromic materials which possess stable and reversible optical changes is a particular challenge.…”
mentioning
confidence: 99%